Réponses

  • Utilisateur Brainly
2014-07-04T21:31:59+02:00
Calculer la dérivée de f(x)=1/x^2 + 2/x^3 +x^1^/^4

1/x^2 + 2/x^3 +x^1/4 est de la forme u + v avec u = 1/x^2  et v =  2/x^3 +x^1/4 or (u + v)' = u' + v'

1/x^2  est de la forme u / v avec u = 1 et v = x^2  or (u / v)' = (u' * v - u * v')/v^2

x^2  est de la forme u ^ n anec u = x et n = 2  or (u ^ n)' = n u' u ^(n-1)

2/x^3 +x^1/4 est de la forme u + v avec u =  2/x^3  et v = x^1/4 or (u + v)' = u' + v'

2/x^3  est de la forme u / v avec u =  2 et v = x^3  or (u / v)' = (u' * v - u * v')/v^2

x^3  est de la forme u ^ n anec u = x et n = 3  or (u ^ n)' = n u' u ^(n-1)

x^1/4 est de la forme u / v avec u = x^1 et v = 4 or (u / v)' = (u' * v - u * v')/v^2

x^1 est de la forme u ^ n anec u = x et n = 1 or (u ^ n)' = n u' u ^(n-1)

D'où 
\boxed{f'(x)=-1(2*x)/(x^2 )^2+- 2(3*x^2)/(x^3 )^2+(1x^0)/4 }